Tomato seedling growth response to different water sources and a substrate partially replaced with dewatered aquaculture effluent - Jason J. Danaher; Jeremy M. Pickens; Jeffrey L. Sibley; Jesse A. Chappell; Terrill R. Hanson; Claude E. Boyd (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The experiment was performed to determine the effect a commercial potting mix partially replaced with dewatered aquaculture effluent had on tomato transplant growth. Methods The experiment was designed as a 2 9 3 factorial and evaluated two water sources (water-soluble, inorganic fertilizer or municipal water) and three soilless substrates with 0, 5 or 10 % dewatered aquaculture effluent (v/v) on substrate properties and tomato (Solanum lycopersicum Mill. âBolsenoâ) transplant growth. The layout was a completely randomized design with twelve single-pot replications for each treatment. Results There was a substrate and water interaction affecting plant height, leaf dry matter (LDM), stem dry matter, root dry matter (RDM), and total dry matter (TDM). Tomato plants watered with inorganic fertilizer and grown in substrates replaced with 0 and 5 % dewatered aquaculture effluent had greater LDM, RDM, and TDM compared to plants watered with municipal water. However, tomato plant growth in substrate partially replaced with 10 % dewatered aquaculture effluent was similar irrespective of water source. Conclusion Substrates incorporated with 10 % aquaculture effluent provided optimal physical and chemical properties along with sufficient nutrients for tomato transplants without the need for commercial, inorganic fertilizer.